2021
DOI: 10.1055/s-0041-1723000
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Biosynthetic Grafts for Aortoiliac Reconstructions in Nonsterile Operative Fields

Abstract: Background Prosthetic vascular grafts placed surgically or via endovascular techniques can be subject to the risk of life-threatening graft infections. The Omniflow II vascular prosthesis is a biosynthetic graft that was reported to have favorable properties in resisting infections. Materials and Methods We retrospectively reviewed our 3 years' experience of using the Omniflow II prostheses for aortoiliac reconstructions in patients considered to carry a substantial risk of subsequent prosthetic graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…14 Nonetheless, experience with the use of biosynthetic collagen prosthesis to treat prosthetic aortic graft infection is still limited, and only case series with small numbers of patients have been reported until now. 8,9,24 However, the reinfection rates with this prosthesis in these studies are low. The study with the greatest number of patients was published in 2021 by El Beyrouti et al, who reported the outcome of 16 patients with aortic graft infection treated with biosynthetic grafts.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…14 Nonetheless, experience with the use of biosynthetic collagen prosthesis to treat prosthetic aortic graft infection is still limited, and only case series with small numbers of patients have been reported until now. 8,9,24 However, the reinfection rates with this prosthesis in these studies are low. The study with the greatest number of patients was published in 2021 by El Beyrouti et al, who reported the outcome of 16 patients with aortic graft infection treated with biosynthetic grafts.…”
Section: Discussionmentioning
confidence: 74%
“…After a mean follow-up of 28.6 months, the reinfection rate was 6.3%. 24 This study has several limitations. The main limitation is the small number of patients and the retrospective design.…”
Section: Discussionmentioning
confidence: 92%
“…Several techniques have been described for the treatment of aortic graft infections, ranging from isolated anti-infection therapy to graft explantation with extensive debridement of all infected tissue followed by revascularization using extra-anatomic bypass or in situ reconstruction [9,[11][12][13][14][15][16]. All these approaches remain challenging because of prolonged operating times, sufficient length of the autologous graft, limited availability of certain prostheses, patency (especially through extra-anatomical bypass), and the risk of re-infection [9,22].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical debridement and replacement of infected segments is necessary, but the close proximity of synthetic grafts to the infected field may lead to high rates of reinfection. Several graft materials for in situ reconstruction (using an antibiotic soaked or rifampicin-bounded graft, cryopreserved allograft, autogenous femoral vein, tube graft made of bovine pericardium, silver-coated prostheses, Omniflow or cryopreserved allograft) have been studied to prevent infection recurrence with variable results [7][8][9][10][11][12][13][14][15][16]. Extra-anatomical bypass techniques (axillo-femoral bypass) have also been proposed but with increased morbidity: low patency (40-73% at 5 years), limb amputation (up to 24%), aortic stump blow-out (2-30%), and mortality (up to 27%) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to comorbidities, porcelain aorta, and a Euroscore II of 10.8, the interdisciplinary heart team opted for transcatheter aortic valve replacement (TAVR). Yet, options for vascular access were severely limited because of a history of an aorto‐bifemoral bypass grafting (Omniflow II ® graft, LeMaitre Vascular, Burlington, USA: biosynthetic composite of ovine collagen and a polyester mesh 1 ) as well as the presence of a severe stenosis of both the left subclavian artery and the brachiocephalic trunk. Based on the relevantly increased individual patient's risk profile for a transapical access and open‐heart surgery, options for transfemoral approach were thoroughly discussed in our team.…”
Section: Figurementioning
confidence: 99%